Using Temporal Sensitivity to Predict Performance Under Latency in Teleoperation. (February 2018) - Scholcover, Federico; Gillan, Douglas J.
Objective: This article establishes a relationship between temporal sensitivity and task performance under one-way latency between input and response. Background: As the latency between human input and telerobot response increases, performance (e.g., speed to complete task and accuracy) declines. Tools, such as predictive displays, have been developed to ameliorate performance costs. However, more work is needed to understand the relationship between individual differences and task performance. Temporal sensitivity in particular was the focus of this research. Method: Participants completed two tasks. In the time estimation task, participants estimated the duration of a series of visual stimuli. In the second task, participants drove a remote-controlled (RC) car through a track. On each trial, there was a latency between the participant's input into the controller and the response by the RC car, with latencies ranging from 400 to 1, 000 milliseconds between trials. Completion time and the number of errors made were recorded. Results: Temporal sensitivity predicted the total number of errors made during a trial but was not found to be a predictor of completion time. It was however predictive of error rate (i.e., errors per minute), suggesting a possible speed/accuracy trade-off. Conclusion: This was an initial step in establishing a link between temporal sensitivity and performance with latency. Application: The study has applications toward training teleoperators who may experience latency, such as astronauts and surgeons.